Antitumor Activities of the Typhonium flagelliforme Extract Combined with Natural Interferons of Canine and Feline in Mice with DMBA Induced Skin Tumors - Harlina, Eva; Sandriya, Ardi; Rostantinata, Riski; Nurcholis, Waras; Sutardi, Lina Noviyanti; Subangkit, Mawar; Ridho, Rachmi; Priosoeryanto, Bambang Pontjo (Jurnal Veteriner; Vol 25 No 2 (2024), 2024)
Indonesia has various plants with potential activities and uses as antitumor agents, one of which is  Typhonium flagelliforme . This study aimed to examine in vivo the effects of combination therapy of  T. flagelliforme  leaf-ethanolic extract and natural interferon of canine or feline as an antitumor agent. In this study, 18 female mice of ddY strain induced with 7.12-dimethyl-benz(?)anthracene (DMBA) carcinogenic substance were divided into six treatment groups. All tumor tissues formed were collected and made for histopathological slides. The slides were stained with Hematoxylin-Eosin (HE) and immunohistochemistry (IHC) procedure using antibodies for proliferating cell nuclear antigen (PCNA) and Caspase-3. The macroscopic observations showed that the skin surface of the mice groups with tumors had alopecia with a reddish color. The microscopic observations showed three tumors types: anaplastic carcinoma, fibrosarcoma, and squamous cell carcinoma. The mitotic, angiogenesis, PCNA and Caspase-3 tests showed significant differences among the groups administered with the single and combination test materials. The combination therapy of  T. flagelliforme  leaf-ethanolic extract and natural interferon can stabilize mice’s body weight, inhibit tumor growth, reduce mitosis and angiogenesis, and reduce PCNA and Caspase-3 expression.